Rationalist Theory in the Postillas de Grammatica Geral of Francisco Sotero dos Reis (Global Journal of Human-Social Science, 2019)
Our goal in this article is to analyze the Postillas de grammmaticageralapplicada lingua portugueza pela analyse dos classicos ouguia para a construc oportugueza Apostilles of General Grammar as Applied to the Portuguese Language Through the Analysis of the Classics or a Guide to Portuguese Construction 1868 1862 by Francisco Sotero dos Reis 1800-1871 in order to investigate to what extent the author applies the foundations of the general theory to the exploration and interpretation of excerpts syntax from literary texts of the Portuguese language collected for analysis We will be working with theory methods and techniques from the Hist ria das IdeiasLinguisticas History of Linguistic Ideas Auroux 2006 2009 Colombat Fournier Puech 2017 Leite 2018 which leads us to treat the grammatical fact selected for analysis as an effect and as a cause the theory that served the interpretation given by the grammarian to that fact
Keywords: philosophical grammar; brazilian philosophical grammar; portuguese language